Investigating speaking tasks in relation to communicative goals: Possibilities and obstacles - Ira Dwijayani; Sita Musigrungsi (Universitas Syiah Kuala, 2022)
Enhancing students' communicative competence is crucial in teaching speaking in Communicative Language Teaching (CLT) classrooms. While relating elements focusing on curriculum, materials, and teachers pay attention to developing the students' communicative competence, obstacles hinder students' communicative skill development. This mixed-methods study aimed to analyze the communicative level of the speaking tasks presented in the teaching materials and how teachers used these tasks to enhance communicative competence. It also investigated teachers' perceived difficulties in teaching speaking in the classroom. The participants were three 11th grade teachers and 54 students from three schools in the southern border area of Thailand. Data collected from speaking task analysis and classroom observation were analyzed based on Littlewood's communicative continuum, and a semi-structured interview was analyzed with an inductive approach. This in-depth information illustrates the communicative level presented in the teaching materials and observed in the classroom, along with obstacles encountered. The findings showed that teacher-made teaching materials mainly focused on forms, while commercial textbooks explored forms and meaning-focused in Littlewood's communicative continuum. However, how teachers used the tasks did not always correspond to the original design presented through teaching materials. Many perceived difficulties in teaching English speaking were found, these include time limitations, students' English proficiency level, teachers' attitude toward the tasks, a lack of school facilities, and exam-oriented teaching and learning. The results of this study are expected to be a consideration for material developers in designing speaking tasks and for English teachers in engaging their students with communicative speaking activities.